Antifungal Activity of the Essential Oil of Tagetes minuta Against Some Fungi of Forestry Importance. Issue 1 (2nd January 2019) - Kumar, Rakesh; Pandey, Amit; Varshney, V.K.
Abstract: The essential oil of T. minuta aerial parts was evaluated for its possible antifungal activities against two plant pathogenic fungi Aspergillus niger and Fusarium solani causing pathogenesis in seeds, seedlings and trees, and Pycnoporous sanguineus causing wood to decay. Minimum fungal colony inhibitory concentrations ranged from 0.12 % - 1.0 %. Essential oil exhibited 100 % inhibition of A. niger at 1 % concentration level while 100 % inhibition of F. solani and P. sanguineus was observed at 0.12 % concentration level. The study revealed that biofungicides and wood preservatives can be developed from essential oil of T. minuta for management of above common pathogenic or wood decay fungi.